Efforts to Resolve Social Conflict in Facing Social Conflict Emergencies in Indonesia - Saifudin, Nur (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The diversity of religions, ethnic identities and cultures in Indonesia has unwittingly created building blocks that disrupt the harmony of social cohesion and interrelationships. Conflicts with ethnic nuances are often associated with a spirit of ethnocentrism and narrow nationalism. Ethnocentrism is a way of thinking that makes one's own group the center of everything and becomes the benchmark for assessing and measuring other groups. Each group is assumed to cultivate its own pride and self-esteem, feel superior, glorify the sanctity of its own group and look down on other groups. Each group thinks that its group's tradition of thinking and acting is the most correct while the traditions of other groups are always viewed with disdain. Misperceptions of subjective culture in responding to the diversity of ethnic, cultural and religious identities in social life can lead to large-scale conflicts that require government intervention in efforts to resolve emergency conflicts in Indonesia.